<span>The expression is missing from the question, but here is the given expression which I got from a similar question.
48 + 54 = ___ ´ (8 + 9)
Theleft-hand side of the equation is:
48 + 54 = 102
Now the right-hand side of the equation:
A </span>× (8+9) = Right-hand side
A × (8+9) = 102
Solving for the unknown variable A,
A × 17 = 102
Dividing by 17 on both sides,
A × 17 ÷ 17 = 102 ÷ 17
A × 1 = 6
A = 6
Hence,
48 + 54 = 6 x (8 + 9)
Answer:
The Second Method
Step-by-step explanation:
APE (Absolute Percentage Error) = absolute difference / actual * 100
APE for First method = 61.93
APE for second method = 54.97
MAPE (Mean absolute Percentage error) = Sum of absolute Percentage error/ Number of observations. ( i.e., 4)
Then,
MAPE for the first method = 61.93 / 4 = 15.482
MAPE for the second method = 54.97 / 4 = 13.472
So, MAPE for second method is less than the MAPE for first method.
Answer:
(c) 0
Step-by-step explanation:
Each of the terms in the expression represents a different transformation of a different trig function. Expressing those as the same trig function can make it easier to find the sum.
__
We can start with the identity ...
cos(x) = sin(x +π/2)
Substituting the argument of the cosine function in the given expression, we have ...
cos(π/2 -θ) = sin((π/2 -θ) +π/2) = sin(π -θ) = -sin(θ -π)
__
The first term, sin(π +θ), is a left-shift of the sine function by 1/2 cycle, so can be written ...
sin(π +θ) = -sin(θ)
The second term is the opposite of a right-shift of the sine function by 1/2 cycle, so can be written ...
cos(π/2 -θ) = -sin(θ -π) = sin(θ)
Then the sum of terms is ...
sin(π +θ) +cos(π/2 -θ) = -sin(θ) +sin(θ) = 0
The sum of the two terms is identically zero.